Alternative Strategies for Effective Utilization of Carbon Dioxide in Dimethyl Ether Synthesis. Issue 5 (1st March 2023) - Babapoor, Aziz; Samimi, Fereshteh; Mirzayi, Behruz; Paar, Meysam
Abstract: Converting CO2 into chemicals, e.g., methanol and dimethyl ether (DME), has been an attractive way to protect the global environment. In this process, the total catalyst volume of the methanol reactor was split into two sections to load the reactors. The catalyst volume of each reactor was optimized by the differential evolution technique. It was concluded that the indirect route yields a higher DME production rate than the direct one, as it produces higher amounts of methanol. CO2 conversions increased by 79 % in the indirect two‐stage process, which resulted in the highest DME production rate of 343 t per day. The results demonstrate how the concept of a two‐stage process in the indirect conversion of CO2 is feasible and beneficial for fuel production. Abstract : The dimethyl ether (DME) production processes in direct, direct two‐stage, indirect, and indirect two‐stage conversion routes were compared. Increased CO2 conversion rates and the highest DME amount were gained in the two‐stage indirect route, demonstrating its superiority over all other processes.